2011
DOI: 10.4161/auto.7.5.14684
|View full text |Cite
|
Sign up to set email alerts
|

DJ-1 regulation of mitochondrial function and autophagy through oxidative stress

Abstract: The dysregulation of mitochondrial function has been implicated in the pathogenesis of Parkinson disease. Mutations in the parkin, PINK1 and DJ-1 genes all result in recessive parkinsonism. Although the protein products of these genes have not been fully characterized, it has been established that all three contribute to the maintenance of mitochondrial function. PINK1 and parkin act in a common pathway to regulate the selective autophagic removal of depolarized mitochondria, but the relationship between DJ-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
100
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(102 citation statements)
references
References 1 publication
2
100
0
Order By: Relevance
“…In addition, DJ-1 can be recruited to mitochondria following oxidative stress and contribute to protection against mitochondrial toxins. However, the loss of DJ-1 leads to alterations in mitochondrial phenotypes, including reduced mtΔψ, increased fragmentation and the accumulation of autophagic markers [14] . Our data demonstrated that RAB induced oxidative stress and dramatic mitochondrial swelling with a decrease in DJ-1 expression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, DJ-1 can be recruited to mitochondria following oxidative stress and contribute to protection against mitochondrial toxins. However, the loss of DJ-1 leads to alterations in mitochondrial phenotypes, including reduced mtΔψ, increased fragmentation and the accumulation of autophagic markers [14] . Our data demonstrated that RAB induced oxidative stress and dramatic mitochondrial swelling with a decrease in DJ-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…RAB stimulates mitophagy in PCa cells and inhibits the PI3K/ Akt/mTOR pathway Because mitochondrial depolarization and the loss of protection against oxidative stress were able to cause severe mitochondrial damage and fragmentation, which was followed by the anchoring of LC3BII autophagolysosomes to mitochondrial membranes (mitophagy) [1,14] , we examined whether RAB could induce mitophagy. First, we visualized the colocalization of mitochondria and autophagolysosomes by electron microscopy of RAB-treated PC3 cells and dramatic mitochondrial swelling at 12 h and 24 h ( Figure 3A).…”
Section: Pca Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, recent studies have reported that DJ-1 inhibits several apoptotic pathways such as pyrimidine tract-binding protein-associated splicing factor (PSF) / 54-kDa nuclear RNAbinding protein (p54nrb) pathway (25) and/or apoptosis signal regulating kinase 1 (ASK1) / homeodomain-interacting protein kinase (HIPK1) / death-domain-associated protein (Daxx) pathway (25,50). Moreover, DJ-1 may act to maintain mitochondrial function during oxidative stress, and thereby alter mitochondrial dynamics and autophagy indirectly (51,52). Based on these observations, we consider that the UCP0054278 / DJ-1 complex may maintain and enhance DJ-1-induced anti-oxidative and anti-apoptotic activation, and these responses may synergistically act to prevent both ROS production and neural cell death.…”
Section: Discussionmentioning
confidence: 99%